USING MS ACCESS 2007 PROGRAM TO CREATE DATABASE FOR LIBRARY - Yersultanova, Z.S.; Aitbenova, A.A. (PUBLISHINGS of Kostanay State Pedagogical University, 2018)
The article is considered to be based on the database access library with access to Access. The information program is a practical part of the data base and is a useful tool for the user. The base data is stored and updated on the computer, and the database administrators are using the easy-to-use interface style software.
Keywords: database; objects; pedagogical condition